2018
DOI: 10.1007/s00424-018-2158-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fibroblasts from hypertrophied right ventricle of pulmonary hypertensive rats

Abstract: Pulmonary arterial hypertension (PAH), which is characterized by an elevation of pulmonary arterial resistance, leads to a lethal right heart failure. It is an urgent issue to clarify the pathogenesis of PAH-induced right heart failure. The present study aimed to elucidate the characteristics of cardiac fibroblasts (CFs) isolated from hypertrophied right ventricles of monocrotaline (MCT)-induced PAH model rats. CFs were isolated from the right ventricles of MCT-injected rats (MCT-CFs) and saline-injected contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…POSTN, which is associated with the development of cardiac fibrosis [17,19], is known to promote the phenotypical change of fibroblasts into myofibroblasts with the increase of α-smooth muscle actin (α-SMA) expression and collagen type I production [10,37,38,39]. In contrast, we previously demonstrated that the phenotype of RVFbs isolated from MCT-injected rats is entirely different from that of myofibroblasts [23]. In the RVFbs, the proliferation, migration and matrix metalloproteinase-9 expression were increased, but the expression of α-SMA and collagen type I was decreased [23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…POSTN, which is associated with the development of cardiac fibrosis [17,19], is known to promote the phenotypical change of fibroblasts into myofibroblasts with the increase of α-smooth muscle actin (α-SMA) expression and collagen type I production [10,37,38,39]. In contrast, we previously demonstrated that the phenotype of RVFbs isolated from MCT-injected rats is entirely different from that of myofibroblasts [23]. In the RVFbs, the proliferation, migration and matrix metalloproteinase-9 expression were increased, but the expression of α-SMA and collagen type I was decreased [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we previously demonstrated that the phenotype of RVFbs isolated from MCT-injected rats is entirely different from that of myofibroblasts [23]. In the RVFbs, the proliferation, migration and matrix metalloproteinase-9 expression were increased, but the expression of α-SMA and collagen type I was decreased [23]. It is thus suggested that POSTN might be involved in the PAH-induced RVF of MCT-injected rats through the regulation of RVFbs functions other than the induction of differentiation into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations